2011
DOI: 10.4103/0300-1652.86139
|View full text |Cite
|
Sign up to set email alerts
|

Indications and outcome of abdominal myomectomy in University of Maiduguri Teaching Hospital: Review of ten year

Abstract: Background:Abdominal myomectomy is a common modality of treatment for large and symptomatic uterine fibroid in women who wish to retain their fertility. Though frequently performed the procedure may still be associated with complications.Materials and Methods:A retrospective review of all patients who had abdominal myomectomy from January 1999 to December 2008 at the University of Maiduguri Teaching Hospital. Information on the Sociodemographic characteristics, indication for the myomectomy, uterine size, pre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 11 publications
(17 reference statements)
5
27
1
Order By: Relevance
“…Duration of surgery longer than 4 hours was significantly related to occurrence of complications (P = 0.004). This was contrary to a report by Geidam et al, from Maiduguri, 4 where duration of surgery was not a significant factor in the development of complications. This is probably because the authors also reported that most of the procedures in the Maiduguri study lasted between 60 and 120 minutes.…”
Section: -22contrasting
confidence: 56%
See 3 more Smart Citations
“…Duration of surgery longer than 4 hours was significantly related to occurrence of complications (P = 0.004). This was contrary to a report by Geidam et al, from Maiduguri, 4 where duration of surgery was not a significant factor in the development of complications. This is probably because the authors also reported that most of the procedures in the Maiduguri study lasted between 60 and 120 minutes.…”
Section: -22contrasting
confidence: 56%
“…Operations are carried out in the gynaecological suites in the main operating theatre and transferred thereafter to the gynaecological ward for postoperative care. Patients are booked for clinic follow-up Where, N = minimum number of subjects that need to be enrolled in the study to have a statistical power of 80% p 0 = proportion of sample with postoperative complications from a similar study, 4 10.9% p 1 = proportion of sample with postoperative complications from this study group, 76.5% q 0 = 1 − p 0 q 1 = 1 − p 1 α = probability of type I error, 0.05 β = probability of type II error, 0.02 z = critical value for a given α or β. Setting power at 80% (the minimum power), N = 128.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 One meta-analysis showed that the laparoscopic approach is associated with longer operating times, less blood loss, less postoperative pain and fewer complications than open conventional myomectomy. 9 The choice of open laparotomy or laparoscopic myomectomy depends upon the availability of facilities and expertise of surgeons. The size and number of fibroids may make laparoscopic myomectomy inappropriate.…”
Section: Introductionmentioning
confidence: 99%